A Comparative Study On Online Marketing Strategies With Reference To Amazon And Flipkart In Twin Cities Of Telangana - Dhriti Kappagantu; Netra Mahindra; Baseedu Sai Sandeep (Feedback International Journal of Communication, 2024)
This comparative study explores the awareness and perceptions of online shoppers regarding the marketing strategies employed by Amazon and Flipkart in the twin cities of Telangana. The research aims to understand how these strategies influence consumer behavior and contribute to the companies' market positioning. In today's fast-paced environment, understanding how leading e-commerce platforms attract and retain customers is crucial. Our findings indicate that Amazon excels over Flipkart in various aspects of online marketing. Amazon's strategic use of social media marketing, continuous advertising, and influencer partnerships effectively engages consumers and promotes its products and services. Furthermore, Amazon's diversification into the entertainment sector with platforms like Amazon Prime Video, Amazon Music, and Amazon Mini TV enhances its customer engagement and broadens its market reach. In contrast, Flipkart's marketing efforts are largely confined to the online promotion of its core products and services, limiting its competitive edge. This study highlights Amazon’s superior marketing approaches and their effectiveness in fostering business growth, while also emphasizing the need for Flipkart to expand and innovate its marketing strategies to better compete. This comparative analysis provides valuable insights for businesses and marketers aiming to enhance their online marketing strategies and understand consumer preferences in a dynamic digital marketplace. The research underscores the significance of integrated marketing efforts, including social media and entertainment engagement, in driving consumer awareness and loyalty in the competitive online retail sector.